New daylight fluctuation control in an optical fiber-based daylighting system. (15th April 2019) - Barbón, A.; Pardellas, A.; Fernández-Rubiera, J.A.; Barbón, N.
Abstract: Daylighting systems have recently been developed as another way to harness solar energy and contribute to the reduction of greenhouse gas emissions. Various technologies can be used in daylighting systems. These technologies differ with respect to the sunlight collection systems and sunlight transmission systems they employ, but have solar luminaires in common. Many factors, such as the fluctuations in the intensity of solar irradiance, limit the efficiency of daylighting systems. This study presents the design, construction and assessment of a daylight fluctuations control for enclosed spaces with no direct access to daylight from side openings. A new control algorithm is proposed for this purpose based on daylighting monitoring and a low cost microcontroller. It also allows communication between several solar luminaires based on long range wireless solutions. The main components of the proposed daylight fluctuation control are: the luminaire, mirror, shaft, frame, stepper motor driver, stepper motor, light sensor, limit switch, XBee and microcontroller. The system uses solar luminaries and dimmable lamps. Tests performed in the laboratory on the system have shown positive results. The different dimming profiles perceived have a linear zone; hence, the perceived changes in brightness are correct. The Just Noticeable Difference is less than 200 ( l x ). And, the solar luminaire efficiency has good results that vary between 71.60 % and 76.44 %, depending on the used step angle. Highligts: This study presents a new daylight fluctuation control system for closed spaces. A new control algorithm is proposed based on a low cost microcontroller. Tests performed in the laboratory on the system have shown positive results.